2014
DOI: 10.1080/00405000.2014.899080
|View full text |Cite|
|
Sign up to set email alerts
|

Sound absorption properties of composite structure with activated carbon fiber felts

Abstract: This paper is intended to study the influence of different factors on the sound absorption properties of composite structure with activated carbon fiber felts. Activated carbon fiber felts made from viscose fiber mats were prepared and later combined with perforated panels to form four different composite sound absorption structures. Based on the transfer function method, the impedance tube was used to test the sound absorption coefficients of composite structure in an acoustic range of 80-6300 Hz frequencies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Chen and Jiang (Chen and Jiang, 2007 ) found that the sound absorption performance of the activated carbon fiber composite is superior to that of other composites. Based on this, Shen and Jiang ( 2016 ), Shen and Jiang ( 2014a , b ) established a sound absorption theory model of activated carbon fiber materials by referring to the circular tube theory model and tested the sound absorption coefficient of the activated carbon fiber sensed in the frequency range of 250–6,300 Hz using a dual-channel impedance tube acoustic analyzer. The result showed that the established sound absorption theory model of activated carbon fiber materials can provide theoretical and technical supports for designing and developing activated-carbon-fiber-based sound absorption materials.…”
Section: Vibration and Noise Reduction Based On The Property Of Soundmentioning
confidence: 99%
“…Chen and Jiang (Chen and Jiang, 2007 ) found that the sound absorption performance of the activated carbon fiber composite is superior to that of other composites. Based on this, Shen and Jiang ( 2016 ), Shen and Jiang ( 2014a , b ) established a sound absorption theory model of activated carbon fiber materials by referring to the circular tube theory model and tested the sound absorption coefficient of the activated carbon fiber sensed in the frequency range of 250–6,300 Hz using a dual-channel impedance tube acoustic analyzer. The result showed that the established sound absorption theory model of activated carbon fiber materials can provide theoretical and technical supports for designing and developing activated-carbon-fiber-based sound absorption materials.…”
Section: Vibration and Noise Reduction Based On The Property Of Soundmentioning
confidence: 99%
“…Recently, Toyoda et al 25 explored the enhancement role of fiber‐based materials in the sound absorption process of MPP/fiber‐based composites. Furthermore, Shen et al 26 combined fiber mat, perforated panel and air layer into four different composites and discussed the effect of the combined structure on the low‐frequency sound absorption properties of the composites. Liu et al 27 calculated the sound absorption coefficients of composites consisting of MPP, porous material and air layer using the transfer function method.…”
Section: Introductionmentioning
confidence: 99%
“…The materials that are commonly used for system of sound absorbing using multi-layer structures with porous materials as perforated panels [5][6][7] or microperforated panels [8][9][10][11][12][13][14][15], as they are resistant to humidity, can be designed to provide wide-band sound absorption. Research on sound absorption of multilayer absorbers using fiber porous layers and perforated panel showed that the composed materials had good acoustic properties at low and high frequencies [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The materials that are commonly used for system of sound absorbing using multi-layer structures with porous materials as perforated panels [5][6][7] or microperforated panels [8][9][10][11][12][13][14][15], as they are resistant to humidity, can be designed to provide wide-band sound absorption. Research on sound absorption of multilayer absorbers using fiber porous layers and perforated panel showed that the composed materials had good acoustic properties at low and high frequencies [5,6]. A model predicting sound absorption of systems with perforated panel, porous material, and air layers indicated that addition of the perforated panel can improve sound absorption coefficients around the resonant frequency, but ones in other frequency ranges decrease [7].…”
Section: Introductionmentioning
confidence: 99%